2016
DOI: 10.13189/ujmsj.2016.040304
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the Patient's Mis-centering on the Radiation Dose and Image Quality in CT Imaging – Phantom and Clinical Study

Abstract: The position of the patient highly influences the functioning of the ATCM in CT imaging. The effect of different mis-centerings on the CTDIvol dose was determined during PMMA and water phantom simulations, which were also used for noise assessment. The results show that a 50 mm mis-centering (with the phantom placed above the isocenter) can cause an increase of the CTDIvol by 47 % associated with the lower standard deviation of the HU signal, whilst a -50 mm mis-centering (with the phantom placed below the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The results by Kalra et al (2009) concur with these results [26]. Furthermore, a study by Sukupova et al (2016) found that within 100 mm of vertical off-centring, there was no substantial change in the CT number; however, with 140 mm or more vertical off-centring, a 20 HU change was recorded [31]. These ndings can be explained whereby the amount of off-centring required to cause a CT number change for a ROI will depend on the alignment of phantom geometry and the bowtie lter size.…”
Section: Vertical Off-centring and Phantom Sizesupporting
confidence: 81%
“…The results by Kalra et al (2009) concur with these results [26]. Furthermore, a study by Sukupova et al (2016) found that within 100 mm of vertical off-centring, there was no substantial change in the CT number; however, with 140 mm or more vertical off-centring, a 20 HU change was recorded [31]. These ndings can be explained whereby the amount of off-centring required to cause a CT number change for a ROI will depend on the alignment of phantom geometry and the bowtie lter size.…”
Section: Vertical Off-centring and Phantom Sizesupporting
confidence: 81%
“…Several studies have investigated the effect of off‐centring on dose and image quality. 8 , 14 , 16 , 18 , 21 , 22 , 24 The importance of these studies aligns with the fact that off‐centring in clinical practice is alarmingly commonplace with one study reporting 95% of patients undergoing thoracic or abdominal CT examinations were vertically off‐centred. 17 A retrospective study of 549 patients by Toth and Ge reported a mean lateral positioning error of 0.0 mm, and from −66 to 34 mm in the vertical direction.…”
Section: Discussionmentioning
confidence: 89%
“… 16 Another study showed a mean value of off‐centring (−43 mm) with the minimum and maximum off‐centring from −88 mm to 16 mm. 24 Studies based on visual estimate centring have shown that patients were off‐centred by a mean of 22, 16 23, 8 25.6 17 and 25‐35 mm 18 below gantry iso‐centre. It is clear from the literature that the centre of mass of the patient tends to be positioned below the scanner centre of rotation, rather than above.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [28] reported that misalignment of the phantom led to an increase in noise and a CT number error of up to 20%. Sukupova et al [29] reported that misalignment by >140 mm resulted in a change in CT number by 20 HU. A recent phantom study by [30] also reported that a deviation of 4.3 HU was obtained from a misalignment of 80 mm with a low-tube voltage.…”
Section: Discussionmentioning
confidence: 99%
“…However, misalignment up to 10 mm does not cause significant artifacts to appear. Several studies have reported that misalignment can cause changes in image noise and dose at certain position within the phantoms or patients [29][30][31][32][33]. Further studies are needed on the influence of misalignment on the emergence of artifacts.…”
Section: Discussionmentioning
confidence: 99%